Humanist humanism: Aziz Nesin’s Yaşar Ne Yaşar Ne Yaşamaz and Kurt Vonnegut’s Slaughterhouse Five - Griffin, Hardy Micajah. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
This project begins by demonstrating how Aziz Nesin and Kurt Vonnegut’s novels are part of a trajectory of humanist works challenging institutionalized bodies of hegemonic discourse. The challenge taken up in writing such works is how to respond without adopting an equally dogmatic stance in response. Vonnegut and Nesin simultaneously absent themselves in the world and exist in and through the work, dissipating in the face of the institutions of hegemony. This existence in the work carries with it a great and exigent failure, for while nothing remains for the dogma to act on, this absence in the world and presence in the work leads to an imbalance between the sacrifice made and the results. These two writers respond to the rise of this challenge and the ensuing failure with their own particular brand of humor—one which is a weapon of critique, a call to arms, an admission of failure, and a transcendent laughter all in one.